2023
DOI: 10.1186/s40662-023-00353-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural changes in the neuroretina are accompanied by mitochondrial dysfunction in a type 2 diabetic mouse model

Christie Hang-I Lam,
Bing Zou,
Henry Ho-Lung Chan
et al.

Abstract: Background Diabetic retinopathy (DR), one of the leading causes of blindness and vision impairment, is suggested to exhibit functional and structural changes in retinal neurons as the earliest manifestation, which could be used to predict the progression of related angiopathy. While neural function and survival rely on proper mitochondrial function, and a growing body of literature has supported the role of mitochondrial dysfunction in the development of DR, how diabetes affects mitochondrial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The protective effect of CoQ10 against diabetic retinal neuropathy is further supported by the histological data, in which CoQ10 treated db/db mice were found to have thicker ONL and INL and higher photoreceptor and cone soma densities compared with their age-matched controls. Our lab and others have previously demonstrated disruption of synaptic structures in second-order neurons at the outer plexiform layer without apparent decreased bipolar cell viability in diabetic mice ( Hombrebueno et al, 2014 ; Lam et al, 2023 ). In this study, the number of rod-bipolar cell dendritic boutons was found to be significantly preserved in CoQ10 treated db/db mice compared to the controls.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The protective effect of CoQ10 against diabetic retinal neuropathy is further supported by the histological data, in which CoQ10 treated db/db mice were found to have thicker ONL and INL and higher photoreceptor and cone soma densities compared with their age-matched controls. Our lab and others have previously demonstrated disruption of synaptic structures in second-order neurons at the outer plexiform layer without apparent decreased bipolar cell viability in diabetic mice ( Hombrebueno et al, 2014 ; Lam et al, 2023 ). In this study, the number of rod-bipolar cell dendritic boutons was found to be significantly preserved in CoQ10 treated db/db mice compared to the controls.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, mitochondrial dysfunction has been observed in various retinal cells, including retinal endothelial cells, Müller cells, and photoreceptor cells under simulated hyperglycemia ( Trudeau et al, 2010 ; Tien et al, 2017 ; Lam et al, 2022 ). Recently, our lab has demonstrated a compromised mitochondrial biogenesis in the retina of db/db mice, in which functional and structural changes in the neuroretina were observed, compared to their non-diabetic heterozygous littermate ( Lam et al, 2023 ). These findings suggested that mitoprotection may be beneficial in ameliorating DR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations